In Search of a General IFPUG-Cosmic Conversion Method (Fountain Journal of Natural and Applied Sciences, 2012)
International Function Point User Group Function Points (IFPUG - FP) is the earliest function size estimation method; however, with the introduction of a more scientific method like the Common Software Measurement International Consortium Full Function Points (COSMIC -FFP) which has a wider applicability than the IFPUG, and both methods using the same measuring unit and principle, the continued relevancy of the IFPUG is called to question. In order to save organizations from losing all their investment because of migrating to using COSMIC, researchers have been trying to explore the possibility of converting the output of one method to the other. Several formulas have been proposed but none that can be generally applied yet. This paper reviews some of the popular conversion formulas that have been suggested so far, then, it used each formula to convert the IFPUG values presented in the different studies to equivalent COSMIC values. The converted COSMIC values are compared to direct measurement values to see a trend or how generalized, consistent and reliable the formulas have a tendency to or could be. It also collated IFPUG and COSMIC values of all the applications used in the different experiments plus three new ones and generated a new formula – a formula borne out of heterogeneous data. The result varied widely and nothing conclusive can be said, though, two of the formulas gave closer estimation range than others. Also, the new formula generated from the fifty eight applications gave improved results over others.Keywords: IFPUG; COSMIC; project estimation